Influence of soil type on chemiresistive detection of buried ANFO - Lefferts, MJ; Castell, MR (Elsevier, 2022)
Ammonium nitrate/fuel oil (ANFO) is one of the most commonly used materials for improvised explosive devices (IEDs). Stand-off ANFO vapour sensors that are small, inexpensive, and easy to use will allow for the detection of IEDs in security and humanitarian settings. Concealment is one of the main challenges of IED detection and increases the need for highly sensitive vapour sensors. Here, percolation networks of polypyrrole (PPy) are used to detect ANFO buried under various types of soil. Percolation networks are used to achieve an improved sensitivity compared to thin film-based vapour sensors, achieving a limit of detection of 73 ± 11 ppbv NH3. The influence on the sensor response of concealment under different soil types, as well as the thickness of the soil layer, is investigated. Reliable detection of ANFO buried under layers of sand or sandy soil is demonstrated at sub-ppm concentrations, however clay is found to act as a significant barrier to the permeability of NH3.